Integrating diabetic retinopathy screening within diabetes education services in Australia's diabetes and indigenous primary care clinics. Issue 6 (11th June 2019) - Atkinson‐Briggs, Sharon; Jenkins, Alicia; Keech, Anthony; Ryan, Christopher; Brazionis, Laima; ,
Abstract: As diabetes occurs in all ethnicities and regions it is essential that retinopathy screening be widely available. Screening rates are lower in Indigenous than in non‐Indigenous Australians. Technological advances and Medicare rebates should facilitate improved outcomes. Use of non‐ophthalmic clinicians, (general practitioners, diabetes educators, health‐workers and endocrinologists) to supplement coverage by ophthalmologists and optometrists would extend retinopathy screening capacity. Diabetes educators are an integral part of diabetes management. Integrating ocular screening and diabetes education in primary care settings has potential to improve synergistically retinopathy screening coverage, patient self‐management, risk factor control, care satisfaction, health economics and sustainability of under‐resourced services.